2014
DOI: 10.1016/j.jwb.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of voluntary environmental management practices by MNE subsidiaries

Abstract: There have been few empirical studies of the determinants of voluntary environmental management practices (VEMPs) of MNE subsidiaries operating in emerging countries. To provide insight on this issue, this study explores the antecedent factors that drive MNE subsidiaries to adopt VEMPs, using data drawn from a key emerging country -Turkey. We would like to thank the editor and two anonymous reviewers for their insightful comments on an earlier version of this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 108 publications
(146 reference statements)
4
84
1
Order By: Relevance
“…The influencing factors include, on the one hand, the organization's global environmental vision and, on the other, the challenges associated with defining operational targets and embedding these in environment practices in a global foodservice organization. The size of the firm can be positively associated with the degree of environmental activity (Hofer et al, 2012) as can the degree of stakeholder interest (Jabbour et al, 2015;Tatoglu et al, 2014). Literature confirms the importance of the positioning of the 'greening' function as a key factor in improving the environmental performance of organizations (Ambec & Lanoie, 2008).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The influencing factors include, on the one hand, the organization's global environmental vision and, on the other, the challenges associated with defining operational targets and embedding these in environment practices in a global foodservice organization. The size of the firm can be positively associated with the degree of environmental activity (Hofer et al, 2012) as can the degree of stakeholder interest (Jabbour et al, 2015;Tatoglu et al, 2014). Literature confirms the importance of the positioning of the 'greening' function as a key factor in improving the environmental performance of organizations (Ambec & Lanoie, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…It offers insight into the rationale and stakeholder perceptions of the positioning and alignment of the environment and HR function across these three European subsidiaries. By comparison, recent research focuses on organizations in the same national context (Chen & Chang, 2013;Hofer, Cantor, & Dai, 2012;Jabbour, Santos, & Nagano, 2010, 2012Jabbour, 2013b;Paillé, Chen, Boiral, & Jin, 2014;Tatoglu, Bayraktar, Sahadev, Demirbag, & Glaister, 2014;Teixeira, Jabbour, & Jabbour, 2012), but do not explicitly examine international differences, whereas this study specifically highlights international management practices with a particular focus on Green HRM.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In previous studies, it has been identified that firms that implemented CEP practices were driven by customer concerns (Henriques and Sadorsky, 1996;Christmann and Taylor, 2001;Tatoglu et al, 2014). Today, consumers are more aware of environmental issues and are forcing firms to take appropriate actions in preserving the environment (Paulraj, 2008).…”
Section: Customersmentioning
confidence: 99%
“…Since the introduction of ISO 14001 EM system, the number of companies acquiring certification has increased remarkably in both developed and emerging countries (ISO, 2008). Notwithstanding the release of new standards and voluntary initiatives, there is a dearth of empirical research investigating the underlying determinants of CEP practices particularly in emerging countries (Zhang et al, 2008;Montiel and Husted, 2009;Vazquez-Brust et al, 2010;Tatoglu et al, 2014), as the bulk of this research still focuses on firms in developed countries. On the whole, firms in emerging countries operate in an environment characterized by institutional voids in which the market ecosystem is underdeveloped or not fully functional, leading to environmental degradation (Khanna et al, 2005).…”
Section: Introductionmentioning
confidence: 99%